Negotiating With The Angry Patient - Chris Ellis (South African Family Practice)
For several years, I was the managing partner of a large general practice clinic. It is an interesting position to occupy in this 21st century of zero tolerance. Expectations are high and delivery is often slow. There is a general increase of complaints against doctors and services and the phenomenon of the angry dissatisfied patient has arisen in the last few decades, so I found myself working as the designated complaints department.